Euro Area Policies : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper focuses on the convergence performance of euro area countries before and after euro introduction. The analysis compares per capita incomes across countries, both for the initial group of twelve countries that adopted the euro before 2002 (the so-called EA-12) as well as the current group of 19 euro area members (EA-19). The convergence process has stalled since the introduction of the euro, except for new euro area members which reduced their income gaps vis-a-vis the founding members until their adoption of the common currency. The convergence of income levels is not a prerequisite for a functioning monetary union, but has been considered an important objective of the European economic integration process. Lagging productivity growth in countries with lower initial GDP per capita is found to be the main explanation for the lack of convergence, suggesting that structural reforms can help to restart the convergence process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet